Heparanase regulates EMT and cancer stem cell properties in prostate tumors - Masola, Valentina; Franchi, Marco; Zaza, Gianluigi; Atsina, Francesca Mansa; Gambaro, Giovanni; Onisto, Maurizio (Frontiers in Oncology, 2022)
Prostate cancer displays a certain phenotypic plasticity that allows for the transition of cells from the epithelial to the mesenchymal state. This process, known as epithelial–mesenchymal transition (EMT), is one of the factors that give the tumor cells greater invasive and migratory capacity with subsequent formation of metastases. In addition, many cancers, including prostate cancer, are derived from a cell population that shows the properties of stem cells. These cells, called cancer stem cells (CSCs) or tumor-initiating cells, not only initiate the tumor process and growth but are also able to mediate metastasis and drug resistance. However, the impact of EMT and CSCs in prostate cancer progression and patient survival is still far from fully understood. Heparanase (HPSE), the sole mammalian endoglycosidase capable of degrading heparan sulfate (HS), is also involved in prostate cancer progression. We had previously proved that HPSE regulates EMT in non-cancerous pathologies. Two prostate cancer cell lines (DU145 and PC3) were silenced and overexpressed for HPSE. Expression of EMT and stemness markers was evaluated. Results showed that the expression of several EMT markers are modified by HPSE expression in both the prostate cancer cell lines analyzed. In the same way, the stemness markers and features are also modulated by HPSE expression. Taken together, the present findings seem to prove a new mechanism of action of HPSE in sustaining prostate cancer growth and diffusion. As for other tumors, these results highlight the importance of HPSE as a potential pharmacological target in prostate cancer treatment.